SISTEM INFORMASI MANAJEMEN SURAT BERBASIS PHP DAN MYSQL DI INSTITUT SENI INDONESIA PADANGPANJANG - Irwan Yusti (Jurnal Sains dan Teknologi: Jurnal Keilmuan dan Aplikasi Teknologi Industri, 2016)
Administrative services mail at ISI Padangpanjang still use the procedures manual by recording the letter into an agenda book, followed by the processing stages of each leader to leader next, this process is done manually by the staff of managers by delivering direct mail to any room leaders and stakeholders, so that the effectiveness of the service is not optimal. Under these conditions made a management information system based mail web using the programming language PHP with MySQL database, the system is built with a user interface design that allows users, processing a letter centered on a database, so that the flow of execution and processing letter will be more quickly and precisely, with The processing system built at ISI Padangpanjang letters of administration will be more effective and can save paper usage. Keywords: Information Systems, PHP, database, MySQL, mail processing